2008
DOI: 10.1097/ico.0b013e31816373c5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Biomicroscopy in Opaque Grafts With Post-Penetrating Keratoplasty Glaucoma

Abstract: Secondary angle closure caused by anterior synechiae formation is one of the important causes of PPKG in eyes with opaque grafts. UBM serves as a useful tool for anterior-segment evaluation in such cases and can help in planning the site for glaucoma filtering surgeries and drainage devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…13,14 Despite the importance of the evaluation of peripheral anterior chamber angle in eyes after PKP, as mentioned in the Introduction, our knowledge of it is still limited probably because of difficulties in the accurate assessment of angle structures through opaque corneas. Dada et al 15 found PAS in 30 (97%) of 31 eyes with IOP elevation after PKP using UBM with 12 clockwise sections. On the other hand, considerably lower prevalence rates of PAS were reported, such as 19 (8%) of 229 eyes 16 or 52 (19%) of 269 eyes 17 after PKP with or without IOP elevation.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 Despite the importance of the evaluation of peripheral anterior chamber angle in eyes after PKP, as mentioned in the Introduction, our knowledge of it is still limited probably because of difficulties in the accurate assessment of angle structures through opaque corneas. Dada et al 15 found PAS in 30 (97%) of 31 eyes with IOP elevation after PKP using UBM with 12 clockwise sections. On the other hand, considerably lower prevalence rates of PAS were reported, such as 19 (8%) of 229 eyes 16 or 52 (19%) of 269 eyes 17 after PKP with or without IOP elevation.…”
Section: Discussionmentioning
confidence: 98%
“…68 Ultrasound biomicroscopy (UBM) may be useful in the evaluation and management of OHTN after penetrating keratoplasty when there is inadequate view at the slit lamp. 69 Anterior segment optical coherence tomography (AS-OCT) provides a similar evaluation of the anterior chamber by utilizing infrared light, which may penetrate a graft that is opaque to visible light. [70][71][72][73] Management Determination of corticosteroid dosing may be equally important to medical and surgical treatment of OHTN.…”
Section: Penetrating Keratoplastymentioning
confidence: 99%
“…UBM serves as a useful tool for anterior-segment evaluation in such cases and can help in planning the site for glaucoma filtering surgeries and drainage devices 40 ( Fig. 16).…”
Section: Secondary Angle Closure After Opaque Graftmentioning
confidence: 99%